Análise genômica comparativa de um clone de trypanosoma cruzi e a cepa parental - Maldonado, Danielle Rodrigues Cortez [UNIFESP] (2016)
The taxon Trypanosoma cruzi consists of genetically heterogeneous populations that differ both in genotypic aspects and phenotypic adaptations and virulence towards the mammalian host. The genetic variability is also reflected in the genome organization. Iinterand intra-strain karyotype heterogeneities have been reported, suggesting that chromosomal rearrangements occurred during the evolution of this parasite. Clone D11 is a single-cellderived clone of the T. cruzi G strain selected by the minimal dilution method and by infecting Vero cells with metacyclic trypomastigotes. In a previous work, we have demonstrated the existence of phenotypic, genotypic and karyotypic differences between clone D11 and the parental G strain. Here we performed intraspecific comparative genomic hybridizations to identify chromosome regions harboring copy number variants in the clone D11 and G strain. The most commonly observed aberrations in the clone D11 were deletions and duplications of small chromosomal segments (<50 kb) which could be mediated by homologous recombination. Most of variants was related to loss of DNA and the unequal distribution of genes between the regions of loss or gain of DNA suggest that multigene families can be involved in recombination events between G strain and clone D11. The karyotypes of clone D11 and G strain differ in both the number and size of the chromosome bands. The chromosomal rearrangements detected by hybridization of chromoblots with chromosome-specific markers were confirmed by aCGH. Based on the aCGH data we suggest mechanisms of recombination to explain the chromosomal rearrangements. Genomic changes detected by aCGH suggest the presence of a dynamic genome that respond to environmental stress by varying the number of gene copies and its distribution in the chromosome. These changes could be present in the original population, a multiclonal population, or have been induced by stress in cloning in a monoclonal population. Our data support the hypothesis of a multiclonal population in T. cruzi. However, current evidence suggests the predominance of segmental aneuploidy in T. cruzi, i.e. involving parts of the chromosome, while in Leishmania events involving the entire chromosome (chromosome aneuploidy) are the most common.